Interlinking SDGs and the bottom-of-the-pyramid through tourism - Sekhar; Valeri, Marco (IGI Global, 2024)
In a world grappling with many challenges, the global tourism and hospitality industries find themselves at a crossroads. Existing strategies fall short of stakeholder expectations, while the immense potential of the industry to address Sustainable Development Goals (SDGs) remains underutilized. Negligible attention from academia towards creating value for the Bottom of the Pyramid (BoP) compounds the issue, hindering the development of strategies essential for SDG achievement. This book, Interlinking SDGs and the Bottom-of-the-Pyramid Through Tourism, presents a compelling exploration of how the tourism industry, with its vast potential, can become a key driver for socio-economic and environmental gains, specifically targeting the BoP market and SDGs.The book emphasizes the scarcity of research on inclusive tourism products for BoP stakeholders and proposes innovative strategies to bridge this gap. It advocates for personalized products, inclusive supply chains, and collaborative processes, underlining the potential of these approaches to not only serve BoP needs but also act as a catalyst for achieving SDGs. Through a series of recommended topics, the book invites researchers, academicians, tourism analysts, and industry practitioners to collaborate on developing practical business models that integrate SDGs and BoP needs. Interlinking SDGs and the Bottom-of-the-Pyramid Through Tourism stands as a call to action for academia and industry stakeholders to unite in creating a sustainable and equitable future through tourism.